Study on Kuwait Environmental Remediation Program (KERP): Remediation Demonstration Strategy - Dhari Al-Gharabally; Aisha- Al-Barood (Current Advances in Chemistry and Biochemistry Vol. 7, 2021)
Kuwait’s desert was heavily damaged by 798 detonated oil wells by Iraqi troops, covering 114 square kilometres. Crude oil flowed from the broken oil wells, generating lakes that contaminated more than 40 square kilometres of land.To prevent the spread of oil, wet and dry oil reservoirs were created in low-lying areas of the desert, and polluted soil piles were created during the recovery process. Contaminated land desert changed soil properties, destroying plants (e.g. biota) and animals, and penetrating deeper into the soil layers, posing a threat to valuable groundwater supplies. These oil lakes are generally made up of dry oil materials, although some features contain semi-liquid oil/sludgy material and are referred to as wet oil lakes. The UN Compensation Commission (UNCC), Kuwait National Focal Point (KNFP), and Kuwait Oil Company (KOC) collaborated on a project to repair approximately 26 million cubic metres of significantly oil-contaminated soils. Demonstration remediation technologies are being pursued as feasible options for developing appropriate action plans for reclaiming heavily contaminated land. The goal of this field demonstration research is to see if proven remediation technologies are viable, applicable, and effective in treating oil-contaminated soil. This project will be undertaken at a number of locations in the KOC’s operational oil fields in South-East Kuwait (SEK) to correct three issues (i.e. wet, dry oil lakes and oil contaminated piles). A successful demonstration of remediation technology will serve as a critical metric for building soil remediation strategy plans for full-scale implementation in SEK and other eligible regions.